2021
DOI: 10.1002/nadc.20214114550
|View full text |Cite
|
Sign up to set email alerts
|

The chemical sciences and the quest for sustainability

Abstract: Two years into the "decade of action“ to achieve the Sustainable Development Goals set by the UN in 2015, how much has been accomplished, and how well is chemistry performing in its intertwined goals of enhancing sustainability and reforming itself?

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Materials Science tends to go beyond the boundaries of a human body and finds its match in global system boundaries. Sustainability has recently attracted political alertness when, in 2015, the UN agreement on Agenda 2030 set seventeen timebound Sustainable Development Goals (SDGs) [3]. For material manufacturing, SDG 9, i.e., Sustainability in Industry, Innovation, and Infrastructure, is of relevance, as is SDG 12, i.e., Responsible Consumption and Production.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Materials Science tends to go beyond the boundaries of a human body and finds its match in global system boundaries. Sustainability has recently attracted political alertness when, in 2015, the UN agreement on Agenda 2030 set seventeen timebound Sustainable Development Goals (SDGs) [3]. For material manufacturing, SDG 9, i.e., Sustainability in Industry, Innovation, and Infrastructure, is of relevance, as is SDG 12, i.e., Responsible Consumption and Production.…”
Section: Introductionmentioning
confidence: 99%
“…For achieving sustainability targets, Mayer et al [21] suggested linking the three concepts of "Process", "Material" (or material product), and "Life" related to the technosphere and biosphere, respectively, with procedures for knowledge generation and presented this approach in the context of consistency strategies related to establishing a circular economy in adhesive bonding technology. Presently, approaches for fostering circular economy in the frame of consistency strategies to advance sustainability [23] tend to be centred around forceful process optimisations [24] as potentially low-hanging fruits, e.g., decarbonising the production of energy [3] or establishing digital tools for advancing processes like production or transport within the supply chain.…”
Section: Introductionmentioning
confidence: 99%